Development of New Parental Behavior Questionnaire: Preliminary Results - Brković, Irma (Array, 2005)
The poster presents the process of development of the new Parental Behavior Questionnaire, along with its psychometric characteristics examined in a pilot research and in a large-scale study on determinants of parental behavior. The initial item pool that consisted of 45 items was presented to 284 school-age children in grades 5th to 8th, as well as to their parents. Exploratory factor analysis showed that the questionnaire measured 6 latent dimensions of parental behavior: Emotionality/Warmth, Psychological Control, Monitoring, Permissiveness, Positive Discipline and Negative Discipline. Based on item analysis a final version of the questionnaire, consisting of 33 items, was constructed. It was applied during the large-scale study on a sample of more than 1000 children and their parents across Croatia. Latent structure of the final version of the PBQ and its psychometric properties are described, and possibilities of the questionnaire applicability and directions for further research are discussed.